The relationship between diet and the incidence of anemia in pregnant women in the third trimester - Muhammad Ihwan Amin; Yuni Purwati; Sarwinanti Sarwinanti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Anemia in pregnant women is a serious health problem because it increases the risk of maternal morbidity and mortality, preterm delivery, and low birth weight infants, especially during the third trimester when iron requirements significantly increase. Dietary patterns play an important role in the incidence of anemia, as inadequate intake of iron-rich foods and supporting nutrients can lead to decreased hemoglobin levels. Therefore, dietary patterns are an important factor associated with anemia among third-trimester pregnant women. Purpose: To determine the relationship between dietary patterns and the incidence of anemia among third-trimester pregnant women. Method: This study employed a quantitative research method with a cross-sectional design. The sampling technique used was purposive random sampling, involving a population of 80 pregnant women and a sample of 48 respondents. Data collection consisted of primary data for the dietary pattern variable, which were obtained using a dietary pattern questionnaire, and secondary data for the anemia variable, which were collected from the Maternal and Child Health (MCH) handbook records. Data were analyzed using the Kendall’s tau statistical test. Results: The results of the statistical analysis using Kendall’s tau test showed a p-value of 0.000, which was less than α = 0.05, indicating a statistically significant relationship between dietary patterns and the incidence of anemia. The correlation coefficient obtained was 0.859, indicating a strong category of relationship. Conclusion: It can be concluded that there is a significant relationship between dietary patterns and the incidence of anemia among third-trimester pregnant women.